Influência de variações morfológicas intra-específicas no conteúdo energético de Hoplias aff. malabaricus (Bloch, 1794) na planície de inundação do alto rio Paraná. - Gimenes, Michele de Faveri (2006)
The purpose of the present study was to identify the morphologic differences of three morphotypes of Hoplias aff. malabaricus. These differences may be related to distinct behavior and in energy content stored in the muscles. Energy and morphological variations associated to subsystems (Ivinheima, Baía, Paraná), environments (rivers, connected lagoons, disconnected lagoons) and sites of the upper Paraná river floodplain, were also evaluated. Samples were performed quarterly from June 2004 to March 2005, in nine locations, distributed along the main channel of rivers Ivinheima, Baía and Paraná, connected lagoons (Patos lagoon, Guaraná lagoon, "ressaco do Pau Véio" and Garças lagoon) and disconnected lagoons (Ventura lagoon and Fechada lagoon). To determine possible relationships among morphotypes in relation to the exploration of resources and to investigate the existence of morphologic differences that can influence energy content, we obtained 32 linear morphometric measures. Then, ecomorphological indexes were created using these morphometric measures. Muscles samples of H. aff. malabaricus had their caloric content determined in calorimeter bomb (Parr, 1261). Significant differences were found in the caloric content among the morphotypes, however the subsystems, environment and place did not influence caloric averages. In general, presented tendencies demonstrate an ecomorphological pattern. Morphotype 1 presented greater potential of natatory ability to capture of preys. Morphotype 2 presented greater maneuverability potential and capture of larger preys. However morphotype 3 presented smaller maneuverability potential and potential to inhabit more open environments, not very structured. The pattern observed for the three morphotypes of H. aff. malabaricus in the upper Paraná river floodplain can help to understand as individuals of the same species reduce competition among them and as this can influence energy allocation.